Decoupling the scholarly journal - Priem, Jason; Hemminger, Bradley H. (Frontiers in Computational Neuroscience, 2012)
Although many observers have advocated the reform of the scholarly publishing system, improvements to functions like peer review have been adopted sluggishly. We argue that this is due to the tight coupling of the journal system: the system's essential functions of archiving, registration, dissemination, and certification are bundled together and siloed into tens of thousands of individual journals. This tight coupling makes it difficult to change any one aspect of the system, choking out innovation. We suggest that the solution is the “decoupled journal.” In this system, the functions are unbundled and performed as services, able to compete for patronage and evolve in response to the market. For instance, a scholar might deposit an article in her institutional repository, have it copyedited and typeset by one company, indexed for search by several others, self-marketed over her own social networks, and peer reviewed by one or more stamping agencies that connect her paper to external reviewers. The decoupled journal brings publishing out of its current 17th-century paradigm, and creates a Web-like environment of loosely joined pieces—a marketplace of tools that, like the Web, evolves quickly in response to new technologies and users' needs. Importantly, this system is able to evolve from the current one, requiring only the continued development of bolt-on services external to the journal, particularly for peer review.